Stent treatment for coarctation of the aorta: intermediate term follow up and technical considerations - Thanopoulos, B (2000)
OBJECTIVE—To report the initial and intermediate term results of stent implantation in children with coarctation of the aorta. PATIENTS AND DESIGN—17 patients with coarctation of the aorta underwent stent implantation (median age 11 years, range 0.4-15 years); six were treated for isolated coarctation, nine for recurrent coarctation (five after surgical repair and four after balloon dilatation), and two for complex long segment coarctation. INTERVENTIONS—The procedure was guided by a second catheter placed transseptally in the left ventricle or the aorta proximal to the coarctation site, for angiographic and haemodynamic monitoring during the procedure. Twenty two stents were implanted in 17 patients. One of the patients with long segment coarctation received four stents and the other three. Palmaz 4014 stents were placed in 11 patients, Palmaz 308 in five, and Palmaz 154 in one. RESULTS—Immediately after stent implantation the peak systolic gradient (mean (SD)) fell from 50.0 (24.5) to 2.1 (2.4) mm Hg (p < 0.05). The diameter of the stenotic lesion increased from 5.1( )(1.5) mm to 13.9 (2.4) mm (p < 0.05). There were no deaths or procedure related complications. At a median follow up of 33 months, no cases of recoarctation were identified, either clinically (0/17; 0%, 95% confidence interval (CI) 0% to 19%) or angiographically (0/13; 0%, 95% CI 0% to 25%). CONCLUSIONS—Stent implantation for the treatment of coarctation of the aorta appears to have very low morbidity and mortality, and reasonable intermediate term results. Long term freedom from recoarctation using this method remains to be determined in comparison with simple balloon dilatation.   Keywords: aortic coarctation; blood vessel prostheses; stents